The role of electronic trading and central filing in the performance of the Iraq Stock Exchange for the period (2008-2018) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The rapid development of information technology and its use in all areas has had a positive impact on all areas, and financial markets have had a share of this development through the use of an electronic trading system to settle transactions, enhance transparency and disclosure in all activities of these markets and revitalize their performance.The reason for choosing this topic is that it is a very important topic for what modern technology addresses in trading operations in financial markets. It is worth noting that these innovations have eliminated the need for direct contact with people, but through the Internet and telephone networks, and the new technology has reduced the costs of building systems New business, entry barriers for new competitors were lowered, as the development in communications technology allowed for faster ordering and transfer of market data to a much larger group of participants, the growth of electronic trading execution systems on an international basis was phenomenal, and new stock markets became almost exclusively electronic It has emerged as a leader in the services industry in the stock markets.The central filing system is a complete work system aimed at ensuring the safety of operations in the financial markets, and its work is very important in the stock market in general in order to complete all trading operations that happen in the market. Therefore, the legislation worked to organize the work of the central filing body and some of them singled out total laws that define a structure This system and everything related to its work.One of the research problems revolves around (does the electronic trading system and the central deposit lead to attracting more potential investors to invest their money in the financial market? And does the electronic trading and central deposit system have an effect in spreading awareness and investment culture among the stock market dealers?), And the research is assumed The electronic trading and central filing systems can have an impact in attracting large numbers of Arab and foreign investors, and in increasing awareness and culture of investors and increasing their investment capabilities.The research concluded with a number of conclusions, perhaps the most important of them is that the use of the electronic trading system as an alternative to the manual trading and deposit system gave great flexibility and different information to brokers, which made it easier for them to know the implemented and unimplemented processes and to conduct an analysis of the conditions of companies whose shares are traded faster and achieve transparency and safety for dealers and investors in the market has Shares in raising the efficiency and speed of dealing in securities, that the Iraqi Depository Center works to settle all operations that take place upon its registration, which increases the increase in the deposit indicators and their interaction according to the activity of the center.The research has come out with a number of recommendations, perhaps the most important of which is that the big and correct procedure of the electronic trading mechanism must be continuous during a future time period, as it has a clear impact by avoiding human errors, granting confidence and spreading culture to investors, and opening new investment fields, and this increased activity results in improvement Increased liquidity and a gradual rise in the efficiency of price information.